N-Acetyl-cysteine causes analgesia by reinforcing the endogenous activation of type-2 metabotropic glutamate receptors - Bernabucci Matteo; Notartomaso Serena; Zappulla Cristina; Fazio Francesco; Cannella Milena; Motolese Marta; Battaglia Giuseppe; Bruno Valeria; Gradini Roberto; Nicoletti Ferdinando (SAGE Publishing, 2012)
Abstract Background Pharmacological activation of type-2 metabotropic glutamate receptors (mGlu2 receptors) causes analgesia in experimental models of inflammatory and neuropathic pain. Presynaptic mGlu2 receptors are activated by the glutamate released from astrocytes by means of the cystine/glutamate antiporter (System xc- or Sxc-). We examined the analgesic activity of the Sxc- activator, N-acetyl-cysteine (NAC), in mice developing inflammatory or neuropathic pain. Results A single injection of NAC (100 mg/kg, i.p.) reduced nocifensive behavior in the second phase of the formalin test. NAC-induced analgesia was abrogated by the Sxc- inhibitor, sulphasalazine (8 mg/kg, i.p.) or by the mGlu2/3 receptor antagonist, LY341495 (1 mg/kg, i.p.). NAC still caused analgesia in mGlu3−/− mice, but was inactive in mGlu2−/− mice. In wild-type mice, NAC retained the analgesic activity in the formalin test when injected daily for 7 days, indicating the lack of tolerance. Both single and repeated injections of NAC also caused analgesia in the complete Freund's adjuvant (CFA) model of chronic inflammatory pain, and, again, analgesia was abolished by LY341495. Data obtained in mice developing neuropathic pain in response to chronic constriction injury (CCI) of the sciatic nerve were divergent. In this model, a single injection of NAC caused analgesia that was reversed by LY341495, whereas repeated injections of NAC were ineffective. Thus, tolerance to NAC-induced analgesia developed in the CCI model, but not in models of inflammatory pain. The CFA and CCI models differed with respect to the expression levels of xCT (the catalytic subunit of Sxc-) and activator of G-protein signaling type-3 (AGS3) in the dorsal portion of the lumbar spinal cord. CFA-treated mice showed no change in either protein, whereas CCI mice showed an ipislateral reduction in xCT levels and a bilateral increase in AGS3 levels in the spinal cord. Conclusions These data demonstrate that pharmacological activation of Sxc- causes analgesia by reinforcing the endogenous activation of mGlu2 receptors. NAC has an excellent profile of safety and tolerability when clinically used as a mucolytic agent or in the management of acetaminophen overdose. Thus, our data encourage the use of NAC for the experimental treatment of inflammatory pain in humans.